2017
DOI: 10.1213/ane.0000000000001634
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Volatile Anesthetic Agents Compared With Standard Intravenous Midazolam/Propofol Sedation in Ventilated Critical Care Patients: A Meta-analysis and Systematic Review of Prospective Trials

Abstract: Volatile-based sedation demonstrates a reduction in time to extubation, with no increase in short-term adverse outcomes. Marked study heterogeneity was present, and the results show marked positive publication bias. However, a reduction in extubation time was still evident after statistical correction of publication bias. Larger clinical trials are needed to further evaluate the role of these agents as sedatives for critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
2
9

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(69 citation statements)
references
References 42 publications
5
53
2
9
Order By: Relevance
“…Today, an increasing number of cancer patients receive surgery and general anesthesia is an unavoidable perioperative care for the surgical cancer population. In addition to induction and maintenance of general anesthesia, volatile anesthetic agents have been increasingly used for long‐term critical care sedation . The results of the present study and of those previous studies imply that the volatile anesthetic isoflurane has potential implications for the perioperative and intensive care of some overwhelmed and systemic inflammatory situations.…”
Section: Discussionsupporting
confidence: 57%
“…Today, an increasing number of cancer patients receive surgery and general anesthesia is an unavoidable perioperative care for the surgical cancer population. In addition to induction and maintenance of general anesthesia, volatile anesthetic agents have been increasingly used for long‐term critical care sedation . The results of the present study and of those previous studies imply that the volatile anesthetic isoflurane has potential implications for the perioperative and intensive care of some overwhelmed and systemic inflammatory situations.…”
Section: Discussionsupporting
confidence: 57%
“…According to our results, it can be assumed that sex is not a determining factor that expresses the need for pharmacological sedation. The mean age in the studies of Jerath et al and Masuda et al were close, with the first one being 40, with a minimum age of 20 years and a maximum of 85, and the second study being 47 years, varying from 9 to 85 years old (14,19). When compared to the mean of our study (18 years), it can be observed that the means were higher; however, variations of ages were close to the present study, which presented ages from 6 to 78 years.…”
Section: Discussionmentioning
confidence: 74%
“…In this study, we used nasal or venous drugs to control anxiety in dentistry (13)(14)(15). The objective was to describe the mechanism of action of the drugs used, not the clinical signs such as blood pressure, oxygen saturation and the type of procedure performed.…”
Section: Discussionmentioning
confidence: 99%
“…Because of these advantageous properties, sevo urane and other inhalational anesthetics are increasingly used as general sedatives for invasive diagnostic and therapeutic procedures, mechanical ventilation and management of agitation in intensive care unit. The concentration required for sedation is approximately one third (0.3 minimum alveolar concentration) of the concentration required for general anesthesia with less incidence of nausea and vomiting 14 . The present study aims to test our hypothesis that inhaling low concentration of sevo urane attenuates the abnormal behaviors and reverses the changes to GABA A R associated proteins in a mice model of MK801induced schizophrenia.…”
Section: Introductionmentioning
confidence: 99%